Detection of Ace-1 gene with insecticides resistance in Aedes aegypti populations from DHF-endemic areas in Padang, Indonesia - HASMIWATI HASMIWATI; SELFI RENITA RUSJDI; EKA NOFITA (Society for Indonesian Biodiversity, 2018)
Hasmiwati, Rusjdi SR, Nofita E. 2018. Detection of Ace-1 gene with insecticides resistance in Aedes aegypti populations from DHF-endemic areas in Padang, Indonesia. Biodiversitas 19: 31-36. Aedes aegypti is distributed widely in West Sumatra as a primary vector of Dengue hemorrhagic fever, especially in Padang City. Synthetic insecticide control is one currently used method to prevent mosquito-borne diseases. The extensive, long-term application of Temephos along with inappropriate dosages, have resulted in the development of resistance in Ae. aegypti populations. Mutation of the Ace-1 gene, encoding an acetyl cholinesterase, is one of the mechanisms that confer resistance to organophosphate (OP). The Temephos resistance status of Ae. aegypti in Padang city has not yet been studied. This study aimed to investigate the resistance status of Ae. aegypti and identify any possible mutation (s) of the Ace-1 gene in Padang city. Ae. aegypti samples were collected in five population in Padang city (Jati (JT), Gunung Pangilun (GP), Lubuk Minturun (LM), Korong Gadang (KG), and Bandar Buat (BB)). The larval susceptibility to Temephos was tested by larval bioassays with Temephos pestanal at 0.02 mg/L dosages. Larval susceptibility was determined by mortality percentage values. The relationship between Ace-1 genotypes and the resistant phenotype was analyzed by percentage of genotype frequency. Out of five populations, assessed by larval bioassays, JT and GP were resistant to Temephos; LM, KG, and BB were tolerant. A total of 50 individuals from larval bioassays were genotyped for Ace-1 gene. Our findings showed that Ace-1 was 495 bp in length. Mutation was not found in the G119S location but in the T506T location. Three alleles in T506T location were detected, including a wild type allele, TT (65.21%), and two mutant alleles, TA (26.08%), AA (8.69%). The use of Temephos showed that some Ae. aegypti populations were resistant, others were tolerant, but no population was vulnerable to Temephos. A novel mutation was detected as substitution in T506T location (ACT>ACA).